Outcome of pregnancy in the morbidly obese woman - Eugene Ngoga; David Hall; Fredd Mattheyse; Debby Grové (South African Family Practice)
Background: Obesity is a growing global health problem. In South Africa, more than half of the adult women are overweight and almost 30% are obese. The problems associated with obesity, such as diabetes, hypertension, thrombo-embolism and coronary heart disease, are well described in the non-pregnant population, but the condition itself holds specific risks during the ante-, intra- and postpartum periods of the pregnant woman. Of particular concern is the intrapartum period. Complications such as slow progress during labour and increased rates of caesarean section are best addressed proactively. For this reason certain sources advocate that all morbidly obese women be referred for evaluation of the pregnancy and planning of labour and delivery by an anaesthetist and a specialist obstetrician. The aim of this study was to determine whether morbidly obese women are at increased risk of adverse outcomes, compared to women with a normal body mass index (BMI).